Volvulus of the ileal pouch–anal anastomosis: a meta-narrative systematic review of frequency, diagnosis, and treatment outcomes. (17th September 2019) - Jawoosh, Muhammad; Haffar, Samir; Deepak, Parakkal; Meyers, Alyssa; Lightner, Amy L; Larson, David W; Raffals, Laura H; Murad, M Hassan; Buttar, Navtej; Bazerbachi, Fateh
Abstract: Background: Proctocolectomy with ileal pouch–anal anastomosis (IPAA) is the surgical procedure of choice for medically refractory ulcerative colitis and familial adenomatous polyposis. While rare, a pouch volvulus can occur. We aimed to determine the frequency, presentation, and management approach of pouch volvulus in patients with IPAA. Methods: A systematic search of published literature was performed by a medical reference librarian on 10 August 2018 and two independent reviewers identified relevant publications, extracted data, and assessed the methodological quality based on a validated tool. A retrospective review of the Mayo Clinic electronic medical records identified one case of pouch volvulus between January 2008 and August 2018. Results: The frequency of pouch volvulus from one large published study reporting long-term outcomes of IPAA was 0.18% (3/1, 700). A total of 22 patients (18 ulcerative colitis) were included (median age 32 years, 73% females). Median time to volvulus after IPAA was 36 months while median interval to volvulus diagnosis from symptom onset was 24 hours. Abdominal pain was the most commonly reported symptom (76%). The diagnosis was made primarily by abdominal computed tomography (13/17 patients, 76%). Endoscopic treatment was successful in 1 of 11 patients (9%). Surgery was performed in 20 patients and pouch-pexy and pouch excision were the most frequent surgical operations. A redo IPAA was performed in five patients (25%). Conclusion: Pouch volvulus is a rare but serious complication of IPAA and should be suspected even in the absence of obstruction symptoms. Endoscopic treatment often fails and surgery is effective when performed early.